1983
DOI: 10.1507/endocrine1927.59.11_1759
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Age Differences in the Spontaneous Release of Gonadotropins from Immature Rat Pituitary Glands In Vitro

Abstract: The present study was carried out to characterize the spontaneous release of LH and FSH from the pituitary gland of infant rats in an in vitro system. In addition, the responsiveness of their pituitary glands to synthetic LHRH in vitro was examined. Wistar-Imamichi male and female rats, aged between 1 and 21 days and androgenized female rats at 7 and 21 days of age were used. One-day-old female rats were androgenized by a subcutaneous injection of 1 mg of testosterone propionate. Animals were killed by decapit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

1986
1986
1986
1986

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…12], In the present study, pituitary LH content was sig nificantly lower in male rats as early as day 0. This is in agreement with the results of Nonaka [22]. Is the sex difference at this time related to an acute testosterone discharge that occurs 0-2 h after birth [7]?…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…12], In the present study, pituitary LH content was sig nificantly lower in male rats as early as day 0. This is in agreement with the results of Nonaka [22]. Is the sex difference at this time related to an acute testosterone discharge that occurs 0-2 h after birth [7]?…”
Section: Discussionsupporting
confidence: 92%
“…The present study has further shown a similar high LH synthetic capacity in female neonatal pitu itary in vivo as well. The rate of hormone accumulation was greater in female rats be tween days 1 and 4, despite higher levels of LH release [5,10,14,15,24], Administra tion of testosterone propionate to female pups is known to lower pituitary LH content [13,22]. Accordingly, lack of circulating tes tosterone is most likely to be responsible for the high LH synthetic activity of the female neonatal rats.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations